A Unique Opportunity to Study Short and Long Term Consequences in Children Prenatally Exposed to Illicit Drugs and Opioid Maintenance Treatment Using Czech and Scandinavian Registers - Gabrhelík, Roman; Nechanská, Blanka; Mravčík, Viktor; Skurtveit, Svetlana; Lund, Ingunn Olea; Handal, Marte (Central European journal of public health, 2016)
Licit and illicit drug use in pregnant women constitutes a long lasting and serious problem worldwide. Information on long-term effects of maternal drug use on the child is limited. Nationwide registers provide a great potential to study short and long-term consequences for children exposed to licit and illicit drugs during pregnancy. We discuss this potential, with a special emphasis on exposure to methamphetamine, heroin and prescription drugs used for opioid maintenance treatment (OMT). We also discuss the advantages of register data and of merging such data from different regions. The Czech and Scandinavian registers are largely comparable and provide great opportunities to conduct innovative research. For instance, using Czech and Scandinavian cohorts we can compare groups with similar characteristics, such as mothers in OMT and mothers addicted to other drugs while also controlling for important confounding factors such as health and socio-economic status.
Keywords: opioid maintenance treatment; dospělí; Pregnancy Outcome; těhotenství; výsledek těhotenství; Humans; methamfetamin; lidé středního věku; Middle Aged; national health registry; zpožděný efekt prenatální expozice; Substance-Related Disorders; Opiate Substitution Treatment; Czech Republic; heroin; poruchy spojené s užíváním psychoaktivních látek; Registries; drug use; Česká republika; Heroin; Illicit Drugs; pregnancy; Adult; registry-linkage study; Infant, Newborn; Scandinavian and Nordic Countries; opiátová substituční terapie; Skandinávie a severské státy; Methamphetamine; methamphetamine; Prenatal Exposure Delayed Effects; registrace; novorozenec; ženské pohlaví; Analgesics, Opioid; lidé; Pregnancy; Narcotic Antagonists; zakázané drogy; opioidní analgetika; narkotika - antagonisté; children; Female